Determinan Audit Delay pada BPKP di Provinsi Sumatera Utara - Zendrato, Julita Roslin Elisabet; Lase, Rini Darma Yanti; Salamah, Choiruna Mardiana; Zain, Jenny; Syahputra, Oky (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Financial reports have an important role for stakeholder users, such as governments, lenders, citizens, investors, and various other interests, as a reference for measuring profits and making decisions. The results of the analysis to determine the components that drive audit delays on audited financial reports. This study analyzes variables such as audit tenure, financial distress, audit opinion, and auditor reputation. This study uses a quantitative objective mechanism and includes primary data and distributes questionnaires to researchers at the BPKP office. The sample of this study consisted of auditors at the BPKP office in North Sumatra Province, totaling 60 active auditors on duty. Based on the findings of this study analysis, audit tenure has no significant impact on the occurrence of audit delays in financial reporting. However, financial distress, audit opinion, and auditor reputation have a significant impact on the occurrence of audit delays. In this regard, this study will help prevent audit delays in financial reports.